Knee joint instability in conditions of congenital malformations of the lower extremities - Khmyzov, Sergij; Yakushkin, Yevgen; Katsalap, Yelizaveta (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
It is impossible to find out the number of patients with knee joint instability (KJI) in case of congenital malformations of the lower extremities (CMLE). Children, adolescents and young people usually adapt well to this abnormality, so they rarely present with symptoms of instability, even with positive tests. The main reasons for the manifestation of KJI in CMLE are inadequate loading, injuries of the lower extremity and surgical correction. Objective. Based on the assessment of the scientific literature to define the KJI terminology, to identify the main causes of its development and clinical manifestations in conditions of CMLE, to identify trends in the treatment tactics. Methods. More than 500 articles from international libraries PubMed, NCBI, Google Scholar, Medscape, MedlinePlus were searched and analyzed. Taken into account the rarity of the abnormality and the small amount of research in recent years, the depth of the search was 25 years. Results. KJI in children with CMLE may be a consequence of congenital structural features of the lower extremity (isolated malformation in the form of agenesis of the cruciate ligaments or inferiority of the ligament of the knee joint in complex abnormality) and complication of surgical correction of longitudinal defects of the extremities. As the abnormality is not well studied, the tactics for such patients still remain the topic of discussion. The expediency of surgical stabilization of the knee joint has not been conclusively proven due to the fact that in the case of its anomalies certain adaptive mechanisms are formed, which on the one hand are not appropriate to violate, and on the other hand, the current level of medicine allows to promote patients’ functional capabilities, inducing KJI progressing. Conclusions. Children with CMLE adapt well to the concomitant KJI, so in everyday life and prior to surgical correction of CMLE, it does not bother patients. Particular attention should be paid to the stability of the knee joint both before and during prolongation and correction of deformity. The variability and severity of CMLE determines the implementation of multi-stage surgical treatment and surgical stabilization of the knee joint to improve extremity function may be one of them. Key words. Children, knee joint instability, congenital malformations, lower extremities, surgical treatment.